The proving ebook - Lewis, Beverly (2017)
Having left the Amish life for the English world, Amanda Dienner is shocked when she learns that her mother has passed and left her Lancaster County's most popular Amish bed-and-breakfast. The catch is she has to run it herself for one year, acting as hostess. Amanda accepts the terms, but coming home to people she left behind won't be easy.